THE PLANTÁGO AND ITS IMPORTANCE IN MODERN MEDICINE - Boymurodov Esan Suyunovich (Web of Journals Publishing, 2025)
Ibn Sina warns that foster care is primarily carried out by the family and parents, and that foster care should be chosen by the parents themselves. It is appropriate to cite the wisdom of Ibn Sina among the people.With the help of natural products, it is good for mothers to treat their children to family members and teach their children to do the same.The Plantágo grows along the road, in villages, yards and gardens. Its beneficial properties were known from the Middle Ages. The Avicenna ( Abu Ali ibn Sino) used the leaves of this plant to stop bleeding against the background of wounds and inflammation. Even since the beneficial properties of the plant have been proven in practical medicine, various drug forms of plantain are effectively used. In the treatment of inflammatory processes in the kidneys and liver, tumors with eye diseases, in the treatment of tumors that do not have a dangerous property, plantain parts were used. Plantágo seeds are recommended by doctors to treat intestinal diseases and deep lung damage.
Keywords: Plantágo, extract, syrup, tincturae, phytobalans, natural antibiotic.